Determinants of bank profitability: evidence from the UK - Xia, Yujing (2019)
This paper examines bank-specific and macroeconomic factors that affect bank profitability. Using an unbalanced panel dataset of 59 UK banks over the period 2011-2018, the paper applies fixed effects (FE) models and the system generalized method of moments (GMM) estimator. Empirical results exhibit that bank profitability is positively determined by cost management efficiency and capital strength. However, banks with more liquidity, higher levels of credit risk and a larger size tend to be less profitable. With regards to macroeconomic determinants, economic growth has no significant impact on bank profits, while inflation and unemployment are negatively related to bank profitability.